Breast-feeding: Current knowledge, attitudes and practices of paediatricians and obstetricians - A. Videlefsky; C. Nikodem; J. Hofmeyr (Curationis, 1996)
Doctors, as part of the healthcare team, can have a significant impact on the successful initiation and maintenance of breastfeeding. There is a need for ongoing education and intervention programmes to update current knowledge on breastfeeding management.